2005
DOI: 10.4049/jimmunol.174.12.7539
|View full text |Cite
|
Sign up to set email alerts
|

Activation of CD8+ Regulatory T Cells by Human Placental Trophoblasts

Abstract: The immunological basis by which a mother tolerates her semi-allogeneic fetus remains poorly understood. Several mechanisms are likely to contribute to this phenomenon including active immune regulation by regulatory T cells. In this article, we report that human placental trophoblasts activate a clonal population of CD8+ T cells with regulatory function. These cells are not MHC class I restricted, but require costimulation through a member of the carcinoembryonic Ag family present on early gestation trophobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 52 publications
5
75
0
2
Order By: Relevance
“…Trophoblasts play central parts in the development and maintenance of a successful pregnancy, as they modulate maternal immune cells to tolerate the fetus (32)(33)(34)(35)(36)(37). Invasive trophoblasts encounter maternal immune cells, particularly NK cells, which aid in uterine tissue invasion and remodeling of uterine spiral arteries (36).…”
Section: Discussionmentioning
confidence: 99%
“…Trophoblasts play central parts in the development and maintenance of a successful pregnancy, as they modulate maternal immune cells to tolerate the fetus (32)(33)(34)(35)(36)(37). Invasive trophoblasts encounter maternal immune cells, particularly NK cells, which aid in uterine tissue invasion and remodeling of uterine spiral arteries (36).…”
Section: Discussionmentioning
confidence: 99%
“…Jenkinsson et al, first reported CD1d transcription in both trophoblast and choriocarcinoma cell lines (Jenkinson et al 1999), which was followed by the demonstration that CD1d is expressed on both the villous and extravillous trophoblasts and that its expression increases as gestation progresses (Boyson et al 2002;Shao et al 2005). In addition to trophoblasts in anchoring villi, CD1d is expressed on trophoblasts that have invaded well into the maternal decidua (Boyson et al 2002).…”
Section: Nkt Cells and Cd1d At The Maternal-fetal Interfacementioning
confidence: 99%
“…Fitting with the immunochemistry analysis, the graftinfiltrating cells contained relatively high numbers of CD103 ϩ cells compared with naive animals (Fig. 3) ϩ T cells with a CD103 ϩ CD45RC Ϫ CD62L low phenotype, a population that has also been described as being potentially regulatory/activated T cells (22,23).…”
Section: The Grafts Of Anti-donor Class Ii-treated Tolerant Recipientmentioning
confidence: 99%